If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -6 + -12a + -4 = -82 Reorder the terms: -6 + -4 + -12a = -82 Combine like terms: -6 + -4 = -10 -10 + -12a = -82 Solving -10 + -12a = -82 Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '10' to each side of the equation. -10 + 10 + -12a = -82 + 10 Combine like terms: -10 + 10 = 0 0 + -12a = -82 + 10 -12a = -82 + 10 Combine like terms: -82 + 10 = -72 -12a = -72 Divide each side by '-12'. a = 6 Simplifying a = 6
| 21(x-1)=7(3-x)1-14 | | 3x-2=-x-10 | | x+y=ywhatisx | | 34x^4-27x^2=0 | | -x+4x=-5x+2x-10 | | 2x+-3=2 | | 9x^2-x-21=0 | | 14.4s-2=6.6s-4.2 | | 6+2x-4=3x-6 | | -3x+6=-5x-8 | | 0.1(x+70)+0.5x=16 | | -2x-2=4-4x | | -20x+4x=72 | | -16x^2-21x+207=0 | | 5/8(x-7) | | 0.2(x+2)=0.1x | | 6x^5-150x^3=0 | | 6x+8-13k+10=4-6x+4x | | x-3=-x-3 | | 4x/2-8/2=2x/6+1 | | 9(x-4)/3=3x+12/9 | | Y=12x+b | | 300=15mx+nforx | | -16x^2-15x+207=0 | | 3+2g=5g-8 | | 4x^8+16x^4+12=0 | | 15-0.75p=13-0.50p | | 13x+12=9x-6 | | .18(y-5)+.14y=.12y-.3 | | X^2=8-16 | | -3x-39=4(5x-4) | | 5(4x-3)=45 |